Endoscopic Findings of Common Gastritis in Koreans - Jung-Hwan Oh (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
In 2013, the Japan Gastroenterological Endoscopy Society introduced the Kyoto classification of gastritis, which is useful to predict Helicobacter pylori infection based exclusively on endoscopic findings. Based on the Kyoto classification of gastritis, gastric mucosal atrophy, endoscopic intestinal metaplasia, hypertrophic gastric folds, nodularity, and diffuse redness may be associated with gastric cancer and H. pylori infection, which are common endoscopic findings in Koreans. Atrophy and intestinal metaplasia are associated with gastric cancer and therefore require attention. Hypertrophic gastric folds, nodularity, and diffuse redness can be associated with current H. pylori infection. The Kyoto scoring system, which is based on endoscopic findings is useful to predict current H. pylori infection and gastric cancer in the absence of biopsy evaluation in clinical settings. A therapeutic strategy for H. pylori infection based on the Kyoto score is expected to reduce the incidence of gastric cancer in Korea and Japan. In this study, we investigated the endoscopic findings commonly observed in Koreans among those defined by the Kyoto classification of gastritis.